Implementasi Sistem Informasi Manajemen Administrasi Biro Haji dan Umroh Mais Tour & Travel - Wahyu Dhani Prayoga; Wiwit Agus Triyanto (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2026)
The rapid development of information technology has encouraged digital transformation in various sectors, including hajj and umrah travel services. Mais Tour & Travel still managed administrative processes manually and semi-digitally, causing data input errors, difficulties in data retrieval, and unsynchronized information between registration, documents, and departure schedules. This community service activity aimed to design and implement a web-based administrative management information system integrating online registration, pilgrim document management, umrah package management, and departure schedule monitoring. The development method adopted the Waterfall model, consisting of requirements analysis, system design, implementation, testing, training, and evaluation. The result of this activity was a web-based system developed using the Laravel framework that integrated administrative processes into a centralized platform. System implementation improved administrative efficiency, reduced data input errors, accelerated document monitoring, and enhanced service quality for pilgrims. In addition, the training provided improved administrators’ ability to operate the system independently. Therefore, this community service activity successfully addressed the administrative problems faced by Mais Tour & Travel.